2012
DOI: 10.1177/0022343312453063
|View full text |Cite
|
Sign up to set email alerts
|

The effects of trust on victimization in Colombia

Abstract: The allegedly complex relationship between trust and victimization has rarely been modeled and, when done, the effect of trust on victimization has been found not statistically significant. This study finds otherwise, estimating an instrumental model with community data from Cali, Colombia. Cali’s dismal levels of victimization were only second to Medellin, the most violent city of the world in the 1990s. But Cali also pioneered a strategy of social capital formation as the backbone of a deliberate public poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Similar positive findings are reported in various contexts with regard to increased altruism, strengthened social cohesion, and greater civic and political participation (De Luca and Verpoorten, 2015a;Gilligan et al, 2014;Voors et al, 2012). Yet, other analyses find a negative association between conflict and social trust (Cuesta and Alda, 2012;De Luca and Verpoorten, 2015b;Kijewski and Freitag, 2018;Rohner et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…Similar positive findings are reported in various contexts with regard to increased altruism, strengthened social cohesion, and greater civic and political participation (De Luca and Verpoorten, 2015a;Gilligan et al, 2014;Voors et al, 2012). Yet, other analyses find a negative association between conflict and social trust (Cuesta and Alda, 2012;De Luca and Verpoorten, 2015b;Kijewski and Freitag, 2018;Rohner et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…It is also expected that the age variable, subdivided into four sub-groups, is negatively correlated with risk of victimization, since younger individuals are more exposed to the risk of victimization than older individuals Alda, 2012;Kassouf, 2013;Scorzafave et al, 2015).…”
Section: Empirical Strategymentioning
confidence: 99%
“…A number of empirical studies have tested the relationship between social capital and crime. In the international literature, one can highlight studies by Akçomak and Weel (2012), Cuesta and Alda (2012), Blanco and Ruiz (2013) and Corbacho et al (2014). In the Brazilian literature, the only empirical analysis that considers the connection between social capital and crime can be found in Peixoto et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cassar, Grosjean, and Whitt (2013), Cuesta and Alda (2012), Luca and Verpoorten (2015), and Rohner, Thoenig, and Zilibotti (2013), yet there is only a handful of studies devoted to the topic of trust in government. These studies found that satisfaction with government services is a strong predictor of trust in government (Askvik, Jamil, and Dhakal, 2011;Hutchison and Johnson, 2011;Sacks and Larizza, 2012;Stoyan et al, 2016), a finding consistent with studies in developed countries.…”
Section: P O L I T I C a L T R U S T A N D S Tat E B U I L D I N Gmentioning
confidence: 99%
“…The use of the community-average as an instrument is based on the idea that social capital usually affects an individual's perception through socialization (Putnam, 1993). This community-level variable is exogenous to individuals because a random person is usually not powerful enough to influence the perception of the leaders at the community level (Cuesta and Alda, 2012). I also included the variable Visit as a part of my over-identification strategy.…”
Section: Modelsmentioning
confidence: 99%